Spectra, stability and labeling of 1‐(5‐carboxypentyl)‐4‐(2‐(N‐ethyl‐carbazole‐3‐yl) vinyl) pyridinium bromide with a large Stokes shift. (6th August 2015) - Gu, Yingchun; Lin, Dayong; Li, Ran; Tang, Yalin; Fei, Xuening; Zhou, Jianguo
Abstract: Carbazole and its derivatives have been widely utilized as a functional building block in the fabrication of the organic medicine, pesticides, materials, etc., because of their excellent solubility, stability and biological activity. In this paper, 1‐(5‐carboxypentyl)‐4‐(2‐(N‐ethyl‐carbazole‐3‐yl) vinyl) pyridinium bromide with a large Stokes shift was synthesized and characterized by 1 H NMR and MS. The UV/vis absorption and fluorescence spectra in different solvents and at different pH values were investigated preliminarily. The photostability and thermostability were also studied and the results showed that the compound was stable. The compound was also used to label bovine serum albumin (BSA) and calf thymus (ct)DNA. The results showed that the fluorescence intensity is enhanced when labeling with BSA and the binding ability is stronger than ctDNA, making it may be used as a biological probe. Copyright © 2015 John Wiley & Sons, Ltd.